Upaya Peningkatan Kemampuan Pengembangan Media Bagi Calon Konselor Melalui Pelatihan Pembuatan Poster Infografis dan Sinemaedukasi - Dwi Ariyanto, Restu; Fithriyah, Imaniyatul; Hasanah, Iswatun; Andry Budianto, Ahmad; Aisa, Anna (Abimanyu : Jornal of Community Engagement, 2022)
The use of innovative BK Media during the COVID-19 pandemic is a challenge that must be faced by the guidance and counseling profession in Indonesia. Students as agents of change are required to be more adaptive in contributing media solutions that are in accordance with the current characteristics of students. However, the majority of students are still not familiar with the use of image and video editing software using a laptop/PC. Other data found is the condition of the use of BK media still using smartphones. Students still experience internet network problems, lack of knowledge of photo or video editing that can be used in providing counseling services. The photo or video editing applications on smartphones that are used include pixellap, snapseet, canva, tiktok, and kinemaster are only used for self-existence not to be used to create BK service content. Based on these problems, it is necessary to hold training on making infographic posters and educational cinema for prospective counselors so that they are able to provide maximum service to students. The methods used include: (1) socialization, (2) training practice, (3) monitoring & evaluation. The results of the training participants' service activities were able to increase the competence of participants in developing infographic poster media and educational cinema. The use of innovative BK Media during the COVID-19 pandemic is a challenge that must be faced by the guidance and counseling profession in Indonesia. Students as agents of change are required to be more adaptive in contributing media solutions that are in accordance with the current characteristics of students. However, the majority of students are still not familiar with the use of image and video editing software using a laptop/PC. Other data found is the condition of the use of BK media still using smartphones. Students still experience internet network problems, lack of knowledge of photo or video editing that can be used in providing counseling services. The photo or video editing applications on smartphones that are used include pixellap, snapseet, canva, tiktok, and kinemaster are only used for self-existence not to be used to create BK service content. Based on these problems, it is necessary to hold training on making infographic posters and educational cinema for prospective counselors so that they are able to provide maximum service to students. The methods used include: (1) socialization, (2) training practice, (3) monitoring & evaluation. The results of the training participants' service activities were able to increase the competence of participants in developing infographic poster media and educational cinema.